2023
DOI: 10.1177/00099228221150604
|View full text |Cite
|
Sign up to set email alerts
|

“I Felt Like I Had Something I Could Do About It”: Pediatric Clinician Experiences With a Food Insecurity-Focused Produce Prescription Program

Abstract: Efforts to address food insecurity (FI) in pediatric clinics have increased over the last decade, particularly after a groundbreaking 2015 American Academy of Pediatrics policy statement supporting universal routine screening and intervening. Produce prescription programs are a novel strategy addressing FI. Limited data exist on effectiveness and feasibility in pediatric clinical settings. This study explored clinician experiences after enrolling patients who completed a produce prescription program in an urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…Thirty-one sources published between 2014 and 2024 were included in the narrative review (Supplemental Table 1), 18, with 84% being published since 2019. 18,[38][39][40][41]43,45,[47][48][49][50][51][52][53][54][55][56][58][59][60][62][63][64][65][66][67] Sources included 22 peer-reviewed articles (71%), 18,38,39,41,43,44,46,[48][49][50][51][52][53]55,56,58,60,61,63,64,66,67 four reports, 45,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-one sources published between 2014 and 2024 were included in the narrative review (Supplemental Table 1), 18, with 84% being published since 2019. 18,[38][39][40][41]43,45,[47][48][49][50][51][52][53][54][55][56][58][59][60][62][63][64][65][66][67] Sources included 22 peer-reviewed articles (71%), 18,38,39,41,43,44,46,[48][49][50][51][52][53]55,56,58,60,61,63,64,66,67 four reports, 45,…”
Section: Resultsmentioning
confidence: 99%
“…18,[38][39][40][41]43,45,[47][48][49][50][51][52][53][54][55][56][58][59][60][62][63][64][65][66][67] Sources included 22 peer-reviewed articles (71%), 18,38,39,41,43,44,46,[48][49][50][51][52][53]55,56,58,60,61,63,64,66,67 four reports, 45,47,59,62 four toolkits, 40,…”
Section: Resultsmentioning
confidence: 99%
“… 16 , 17 “Food as Medicine” interventions, including medically tailored meals/groceries and produce prescriptions, are frequently integrated into clinical systems and are an emerging and promising method to address not only FI but also nutrition security. 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers engaged in these programs have reported that although there were challenges related to staff time, they perceived an increase in knowledge, confidence, and motivation to screen and address food insecurity. They also appreciated that programs provided a tangible way to assist their patients, especially for under-resourced patients who might not qualify for other assistance programs or in times of emergency ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%